Gastrointestinal injury in cardiopulmonary bypass: current insights and future directions - Mao, Qi-Long; Yu, Zi-Hang; Nie, Liang; Wang, Fei-Xiang; Dong, Yu-Hui; Qi, Xiao-Fei (Frontiers in Pharmacology, 2025)
Cardiopulmonary bypass (CPB) is an essential component of cardiac surgery. As CPB technology continues to advance and innovate, it has enabled the expansion of surgical boundaries and the resolution of many previously inoperable challenges. However, the occurrence of various complications during CPB warrants attention, with their prevention and management being paramount. The gastrointestinal tract, directly connected to the external environment, is vulnerable not only to external factors but also to internal changes that may induce damage. Both preclinical and clinical research have demonstrated the incidence of gastrointestinal injuries following CPB, often accompanied by dysbiosis and abnormal metabolic outputs. Currently, interventions addressing gastrointestinal injuries following CPB remain insufficient. Although recent years have not seen notable progress in this field, emerging academic research underscores the essential role of the gut microbiome and its metabolic products in sustaining overall health and internal equilibrium. Notably, their significance as the body’s “second genome” is increasingly recognized. Consequently, reevaluating the gastrointestinal damage post-CPB, alongside the associated dysbiosis and metabolic disturbances, is imperative. This reassessment carries substantial theoretical and practical implications for enhancing treatment strategies and bettering patient outcomes after CPB. This review aims to deliver a comprehensive synthesis of the latest preclinical and clinical research on CPB, address current challenges and gaps, and explore potential future research directions.